2009
DOI: 10.1007/s10606-008-9085-4
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Advocacy: An Approach for Integrating Diverse Perspectives in Anomaly Response

Abstract: This paper contrasts cooperative work in two cases of distributed anomaly response, both from space shuttle mission control, to learn about the factors that make anomaly response robust. In one case (STS-76), flight controllers in mission control recognized an anomaly that began during the ascent phase of a space shuttle mission, analyzed the implications of the failure for mission plans, and made adjustments to plans (the flight ended safely). In this case, a Cooperative Advocacy approach facilitated a proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Resilience refers to the ‘ability to absorb strain and preserve (or improve) functioning despite the presence of adversity … [and] to recover or bounce back from untoward events’ (Sutcliffe & Vogus, , p. 96). Enacting resilience involves engaging with the reality of difficult situations and actively searching for and reporting errors or other unexpected problems (Watts‐Perotti & Woods, ; Weick et al., ) rather than avoiding or merely surviving adversity. Resilience also entails cultivating and using resources (e.g., emotional, social, technical, capital) flexibly to enact new, adaptive responses (Caza & Milton, ; Coutu, ; Fredrickson, Tugade, Waugh, & Larkin, ; Kahn, Barton, & Fellows, ; Powley, ; Rerup, ).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience refers to the ‘ability to absorb strain and preserve (or improve) functioning despite the presence of adversity … [and] to recover or bounce back from untoward events’ (Sutcliffe & Vogus, , p. 96). Enacting resilience involves engaging with the reality of difficult situations and actively searching for and reporting errors or other unexpected problems (Watts‐Perotti & Woods, ; Weick et al., ) rather than avoiding or merely surviving adversity. Resilience also entails cultivating and using resources (e.g., emotional, social, technical, capital) flexibly to enact new, adaptive responses (Caza & Milton, ; Coutu, ; Fredrickson, Tugade, Waugh, & Larkin, ; Kahn, Barton, & Fellows, ; Powley, ; Rerup, ).…”
Section: Discussionmentioning
confidence: 99%
“…NASA's Mission Control Center in Houston is a positive case study for this capability, especially how Space Shuttle mission controllers developed skill at handling anomalies, expecting that the next anomaly they would experience was unlikely to match any of the ones from the past that they had practiced or experienced. 7 IT-based companies exist in a pressurized world where technology, competitors, and stakeholders change. Their success requires scaling and transforming infrastructure to accommodate increasing demand and build new products.…”
Section: David D Woods and John Allspawmentioning
confidence: 99%
“…Handling anomalies in risky worlds such as space mission operation centers is one example. 7 But studies of joint activity also reveal that the costs of coordination can offset the benefits of involving multiple people and automation in situation management. 5 This earlier research looked at anomaly response anchored in physical control rooms where responders were collocated in open workspaces.…”
Section: Controlling the Costs Of Coordination In Joint Activitymentioning
confidence: 99%
“…Herein lies the crux of the issue: The collaborative interplay and synchronization of roles is critical, 12,13,15 but prior research has shown poor coordination design incurs cognitive costs for practitioners, specifically, the additional mental effort and load required to participate in joint activities. 5,6 This can be particularly exacerbated in the digital services domain where it plays out across geographically distributed groups.…”
mentioning
confidence: 99%